APOE ε4 allele, along with G206D-PSEN1 mutation, alters mitochondrial networks and their degradation in Alzheimer’s disease - Costa-Laparra, Irene; Juárez-Escoto, Elena; Vicario, Carlos; Moratalla, Rosario; García-Sanz, Patricia (Frontiers in Aging Neuroscience, 2023)
Introduction Alzheimer’s disease remains the most common neurodegenerative disorder, depicted mainly by memory loss and the presence in the brain of senile plaques and neurofibrillary tangles. This disease is related to several cellular alterations like the loss of synapses, neuronal death, disruption of lipid homeostasis, mitochondrial fragmentation, or raised oxidative stress. Notably, changes in the autophagic pathway have turned out to be a key factor in the early development of the disease. The aim of this research is to determine the impact of the APOE allele ε4 and G206D-PSEN1 on the underlying mechanisms of Alzheimer’s disease. Methods Fibroblasts from Alzheimer’s patients with APOE 3/4 + G206D-PSEN1 mutation and homozygous APOE ε4 were used to study the effects of APOE polymorphism and PSEN1 mutation on the autophagy pathway, mitochondrial network fragmentation, superoxide anion levels, lysosome clustering, and p62/SQSTM1 levels. Results We observed that the APOE allele ε4 in homozygosis induces mitochondrial network fragmentation that correlates with an increased colocalization with p62/SQSTM1, probably due to an inefficient autophagy. Moreover, G206D-PSEN1 mutation causes an impairment of the integrity of mitochondrial networks, triggering high superoxide anion levels and thus making APOE 3/4 + PSEN1 fibroblasts more vulnerable to cell death induced by oxidative stress. Of note, PSEN1 mutation induces accumulation and clustering of lysosomes that, along with an increase of global p62/SQSTM1, could compromise lysosomal function and, ultimately, its degradation. Conclusion The findings suggest that all these modifications could eventually contribute to the neuronal degeneration that underlies the pathogenesis of Alzheimer’s disease. Further research in this area may help to develop targeted therapies for the treatment of Alzheimer’s disease.